Low gastrointestinal tract bleeding secondary to low-grade gastrointestinal stromal tumor: case report - Caprielova, Yuri Jiménez; Izaguirre, Adrián Aguilar; Chavarria, Eduardo Israel Vega; Arenas, Samuel Rodríguez Gómez; Bezies, Yamir Ahmed Nacud (International Surgery Journal, 2022)
Gastrointestinal stromal tumors (GIST) are neoplasms of mesenchymal origin. We present the case of a patient with low gastrointestinal tract bleeding secondary to a gastrointestinal stromal tumor, as well as her diagnostic clinical approach in a third-level medical unit, as well as a brief review of the literature. The treatment of this neoplasm is surgical and ideally consists of complete resection with negative margins (R0). GISTs mostly affect patients between 4-6 decades of life with a slight predominance in women, with the stomach and small intestine being the most frequently affected organs. The immunohistochemical study shows positivity for c-KIT and CD34 in 100% and 63% of cases. The treatment is surgical which usually by maintaining free margins is curative